Ethiopia : Second Urban Local Government Development Program as a Program-for-Results Operation - World Bank (Washington, DC, 2014)
The second Urban Local Government Development Program (ULGDP II) will enhance the institutional performance of participating ULGs in developing and sustaining urban infrastructure and services, through provision of three interlinked and mutually strengthening tools: (i) Performance-based investment grants, (ii) objective and neutral annual performance assessments, linked to the size of allocations and (iii) comprehensive capacity building support to the cities and to the regions to enhance their capacity in supporting ULGs as well as support to the implementing agency. The Ministry of Urban Development, Housing and Construction (MUDHCo, the Ministry) will be the agency in charge of the Program, as under ULGDP. The Ministry will be supported in areas of capacity building framework for regions, monitoring, reporting and project management and the Program also encompass capacity building to the Ministry to perform its core role related with the Program objectives.